PENGARUH VARIASI PERSENTASE BIOETANOL DARI KULIT PISANG HIJAU PADA BAHAN BAKAR PERTAMAX TERHADAP DAYA MOTOR BENSIN : THE EFFECT OF VARIATION OF PERCENTAGE OF GREEN BANANA PEEL BIOETHANOL IN PERTAMAX FUEL ON GASOLINE MOTOR POWER - Adryansa, Ivan; Firdaus, Ahmad Hanif (Program Studi Teknik Mesin PSDKU Polinema Kediri, 2024)
The availability of fossil fuels is decreasing day by day, therefore it is necessary to renew, one of which is by replacing the main ingredient using renewable materials, one of which is bioethanol. The purpose of this study was to determine the effect of variations in the percentage of bioethanol in Pertamax fuel on the power of gasoline engines. The method used in this study is an experimental method with variations in the concentration of the bioethanol mixture with Pertamax, namely 15%, 20%, 25% in a 125 cc gasoline engine at engine speed of 2000 to 7000 Rpm. Get the best results from the mixture where the 25% bioethanol mixture in the power test is 8,6 Hp at 7000 Rpm rotation.